THE PRACTICE OF TEACHER WRITTEN CORRECTIVE FEEDBACK ON STUDENTS' WRITING: A case study in a senior high school in Bandung - Rubia'tul Khumaeroh, - (2022)
This study aimed to investigate how teacher written corrective feedback (TWCF) helped EFL students in writing recount texts. This research employed a case study design involving 10 students in one private senior high school in Bandung. Documents, namely students' first drafts, TWCF on students' first drafts, and students' final drafts were used to collect the data. The data analysis was conducted based on the comparison of students' recount texts in the first drafts and in the final drafts. The reduction of errors in writing recount text was seen in students' final drafts after students revised their recount texts based on the feedback given. Content, grammar, and mechanics were commented on students' recount texts using the scheme used by Storch and Tapper (2000). The result indicated that TWCF was able to facilitate students' writing in terms of content, grammar, and mechanics in writing class because it could help them produce better texts in their final drafts. Notwithstanding those advantages of TWCF, this study recommended the teacher provide written corrective feedback on paragraph organization since it is also one of the important parts of writing aspects. In addition, it would be better if the teacher could also provide oral feedback to avoid confusion since students need more explanation regarding the given teacher written corrective feedback. Thus, providing different TWCF strategies could be worth to consider so that TWCF enactment could be well-implemented and practiced to make students' writing better in the future.